Postnatal maternal mental health and postnatal attachment - Aileen O'Mahony; Carol Stephens; Vicki Livingston; Eugene Dempsey; Geraldine Boylan; Deirdre Murray (James Cook University, 2023)
Aims: Maternal mental illness has a significant influence on negative maternal and childhood outcomes. Few studies have focused on both maternal depression and anxiety, or explored the interplay of maternal mental illness and the mother-infant bond. We aimed to examine the relationship between early postnatal attachment and mental illness at 4 and 18 months postpartum. Methods: This was a secondary analysis of 168 mothers recruited from the BabySmart Study. All women delivered healthy term infants. Depression and anxiety symptoms were measured via the Edinburgh Postnatal Depression Scale (EPDS) and Beck's Depression and Anxiety Inventory at 4 and 18 months respectively. Maternal Postnatal Attachment Scale (MPAS) was completed at 4 months. Negative binomial regression analysis investigated associated risk factors at both time points. Results: The prevalence of postpartum depression fell from 12.5% at 4 months to 10.7% at 18 months. Anxiety rates increased from 13.1% to 17.9% at similar time points. At 18 months, both symptoms were new in almost two-thirds of women, 61.1% and 73.3% respectively. There was a strong correlation between the anxiety scale of the EPDS and the total EPDS p-score (R=0.887, p<0.001). Early postpartum anxiety was an independent risk factor for later anxiety and depression. High attachment scores were an independent protective factor for depression at 4 months (RR=0.943, 95%CI: 0.924-0.962, p<0.001) and 18 months (RR=0.971, 95%CI: 0.949-0.997, p=0.026), and protected against early postpartum anxiety (RR=0.952, 95%CI: 0.933-0.97, p<0.001). Conclusion: The prevalence of postnatal depression at 4 months was similar to national and international rates, although clinical anxiety increased over time with almost 1 in 5 women scoring in the clinical anxiety range at 18 months. Strong maternal attachment was associated with decreased reported symptoms of both depression and anxiety. The effect of persistent maternal anxiety on maternal and infant health needs to be determined.